Outcomes of the Development for Children with Hearing Impairment Post cochlear Implantation, Rajavithi Hospital - Boonmee, Supranee (Journal of The Department of Medical Services, 2024)
Background: Children born with severe hearing loss are deaf in both ears, which affects speech and language development. Cochlear implant helps with hearing rehabilitation. Due to the situation of COVID - 19 affecting the world, commuting to the hospital could lead to a risk of infection. As a result, children with cochlear implants need rehabilitation to hear continuously. Objective: To study the hearing ability of children with hearing impairment, post - cochlear implants, and to compare the development of listening ability in children with hearing impairment post - cochlear implants who received an auditory - verbal training (AVT) at a hospital, as well as AVT combined with onsite and online training. Methods: A retro - prospective descriptive study on 51 children under five, with post - cochlear implants was conducted from January 2005 to August 2021, using the patients’ medical records. Tools used to collect data records were The Categories of Auditory Performance - II, developed by Gilmore L. Scoring according to CAP - II has 10 levels, i.e., 0 - 9. Data were analyzed using descriptive statistics to examine the frequency, mean, as well as standard deviation. The statistics used for comparison were repeated measures ANOVA, paired - samples t - test, and hypothesis testing. The result showed a statistical significance of p < .05. Results: It was found that there was an increase in hearing ability of the research subjects with post - cochlear implantation. AVT combined with onsite and online training improved listening ability better than on - site - only AVT. Conclusion: There are many factors that impact the hearing ability of deaf children after cochlear implantation. It depends on the duration of the cochlear implant. ;the longer you wear it, the more exposure to language input, the better your listening experience will become. A good cooperation in auditory - verbal practice training combined with onsite & online improved their listening ability more than those who received auditory - verbal training (AVT) in a hospital onsite only. It also helps children post - cochlear implants have good language development.